Pore-Scale Characterization and Simulation of Porous Electrode Material for Vanadium Redox Flow Battery: Effects of Compression on Transport Properties - Xiao, Liusheng; Luo, Maji; Zhu, Lijun; Duan, Kangjun; Bevilacqua, Nico; Eifert, László; Zeis, Roswitha; Sui, Pang Chieh (Journal of The Electrochemical Society, 2020)
In this study, X-ray computed tomography (XCT) and pore-scale simulation were employed to investigate the mechanical deformation of a porous electrode material for a vanadium redox flow battery during compression and to quantify its impact on the effective transport properties of the electrode. Pore-scale simulations using the finite element method (FEM), pore-scale modeling (PSM), and lattice Boltzmann method (LBM) were adopted to obtain the deformed geometry and to compute the effective diffusivity, conductivity, and permeability. The structure of a carbon felt was first scanned and reconstructed by XCT; using the results, a 3D model was generated and meshed for solid mechanics simulations. In the FEM simulation, the displacement of the microstructure at different compression ratios (CRs) was investigated considering the contact, friction, extrusion, and bending interactions between the carbon fibers. The relationship between the CR and transport properties was quantified using in-house PSM and LBM codes. The results reveal that the carbon felt is highly anisotropic. When compressed, the displacement of the carbon fibers changes significantly in the through-plane and in-plane directions. The effective diffusivities and permeability of the felt decrease with increasing CR, and its electrical conductivity increases with increasing CR. The present study demonstrates a workflow that combines experimental characterization and solid mechanics simulation to produce deformed solid mechanics models, which can be subsequently employed for mesoscopic simulations in order to obtain effective transport properties. This approach will enable computational investigations into general porous electrode materials, and more importantly, it can be employed to design new materials that can be engineered for optimal performance.
CRIS-Team Scopus Importer:2023-08-01